Clinical characteristics and postoperative seizure outcome in patients with mild malformation of cortical development and oligodendroglial hyperplasia. (11th October 2021) - Gaballa, Ahmed; Woermann, Friedrich G.; Cloppenborg, Thomas; Kalbhenn, Thilo; Blümcke, Ingmar; Bien, Christian G.; Fauser, Susanne
Abstract: Objective: We describe for the first time clinical characteristics in a series of 20 pre‐surgically investigated patients with mild malformation of cortical development with oligodendroglial hyperplasia (MOGHE) who were operated on in our epilepsy center. We aimed to better diagnose this entity and help surgical planning. Methods: Data on 20 patients with histologically confirmed MOGHE were retrospectively evaluated as to age at epilepsy onset and operation, seizure semiology, magnetic resonance imaging (MRI) localization, electroencephalography (EEG) patterns, extent of the operative resection, and postoperative seizure outcome. Results: Epilepsy began mainly in early childhood; however, symptoms did not manifest until adolescence or adulthood in 30% of patients. All patients had pathologic MRI findings. In 45% of patients the lesion was initially overlooked. Most commonly, the lesion was seen in the frontal lobe. Seizure semiology was characterized as follows: (1) epileptic spasms at epilepsy onset were common and (2) nocturnal hyperkinetic seizures during the course of the disease were rare. EEG always showed frequent interictal epileptic discharges. Two peculiar patterns were observed: (1) during sleep stage I‐II, sub‐continuous repetitive (0.5–1.5/s) unilateral plump spike/polyspike slow waves were seen and (2) during wakefulness, unilateral paroxysms of 2–2.5/s spike‐wave complexes occurred. In total, 60% of patients were seizure‐free 1 year postoperatively. Postoperative seizure outcome was positively correlated with the extent of resection, age at epilepsy onset, and age at operation. Postoperative long‐term outcomes remained stable in patients undergoing larger operations. Significance: MRI, EEG, and semiology already contribute to the diagnosis of probable MOGHE preoperatively. Because postoperative seizure outcomes depend on the extent of the resection, prior knowledge of a probable MOGHE helps to plan the resection and balance the risks and benefits of such an intervention. In patients undergoing larger operations, epilepsy surgery achieved good postoperative results; the first long‐term outcome data were stable in these patients.